Analysis of Mitochondrial Calcium Retention Capacity in Cultured Cells: Permeabilized Cells Versus Isolated Mitochondria - Jang, Sehwan; Chapa-Dubocq, Xavier R.; Fossati, Silvia; Javadov, Sabzali (Frontiers in Physiology, 2021)
In response to various pathological stimuli such as oxidative and energy stress accompanied by high Ca2+, mitochondria undergo permeability transition (PT) leading to the opening of the non-selective PT pores (PTP) in the inner mitochondrial membrane. Opening of the pores at high conductance allows the passage of ions and solutes <1.5 kD across the membrane, which increases colloid osmotic pressure in the matrix leading to excessive mitochondrial swelling. Calcium retention capacity (CRC) reflects maximum Ca2+ overload of mitochondria that occurs just before PTP opening. Quantification of CRC in cultured cells is important for elucidating the effects of different pathological stimuli and the efficacy of pharmacological agents on the mitochondria. Here, we performed a comparative analysis of CRC in isolated mitochondria and permeabilized H9c2 cardioblasts in situ to highlight the strengths and weaknesses of the techniques. The cells were permeabilized by digitonin or saponin, and the Ca2+-sensitive fluorescence probe Calcium Green-5N was used in both preparations. Results demonstrated the interference of dye-associated fluorescence signals with saponin and the adverse effects of digitonin on mitochondria at high concentrations. Analysis of the CRC in permeabilized cells revealed a higher CRC in the saponin-permeabilized cells in comparison with the digitonin-permeabilized cells. In addition, the mitochondrial CRC in saponin-permeabilized cells was higher than in isolated mitochondria. Altogether, these data demonstrate that the quantification of the mitochondrial CRC in cultured cells permeabilized by saponin has more advantages compared to the isolated mitochondria.